Determination of Lipophilicity of Allyl Thiosemicarbazide, N1-Thiocarbamylamidrazone Derivatives, and their Cyclic Products by RP-HPLC, RP-TLC, and Theoretical Methods: Effects of Selected Compounds on the CNS of Mice - Strzemecka, Leokadia; Hawrył, Anna; Świeboda, Ryszard; Hawrył, Mirosław; Jagiełło-Wójtowicz, Ewa; Piątkowska-Chmiel, Iwona; Herbet, Mariola; Chodkowska, Anna (Journal of liquid chromatography & related technologies, 2015)
The allyl thiosemicarbazide, N 1 -thiocarbamylamidrazone derivatives, and the products of their cyclization: the 1,2,4-triazole, 1,3,4-thiadiazole, 1,2,4-triazole[3,4-b]1,3-thiazine, 1,2,4-triazole[3,2-b]1,3-thiazine, 1,3,4-thiadiazole[3,2-a]pyrimidine, 5,6-dihydrothiazolo[2,3-c][1,2,4]triazole, and benzoic acid derivatives have been analyzed by RP-HPLC and RP-TLC methods using the methanol-water mixtures as the mobile phase and the octadecyl stationary phase. The lipophilicity was expressed as the chromatographically derived descriptors: mean of k (mk), mean of logk (mlogk), logk W , S, and ϕ 0 , scores of k, logk, and R M corresponding to the first principal component. Additionally, the authors propose to introduce a descriptor (logk m ) corresponding to the residual specific interactions. Chromatographic parameters of lipophilicity were compared with the partition coefficient (logP) calculated by various softwares (milogP, clogP, AlogPs, AClogP, AlogP, MlogP, KOWWIN, XlogP2, XlogP3). The matrices were created with logk W or R MW and logP and they have been the subject of PCA analysis. The effects of the selected compounds on the central nervous system (CNS) of mice were studied.